Rhodes University students' experiences of living as students on National'Student Financial Aid Scheme (NSFAS) funding - Mgwili, Thab'sile (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
This study explores Rhodes University students' experiences of living as students on National Student Financial Aid Scheme (NSFAS) funding. The Marxist theoretical framework critique of neoliberalism and welfare systems is used. The Marxist theory is the main theory that underpins the study. Eighteen participants were involved in an in-depth interview process. Out of 18 participants, one is a staff member at Rhodes University Financial Aid Office. The key findings of this research revealed the unfavorable circumstances of students on NSFAS at Rhodes University. Secondly, it was discovered that students shared similar sentiments as NSFAS and DHET: They recognize the major areas that need to be addressed by NSFAS. Thirdly, NSFAS had to some extent made a positive contribution to the higher education sector. Suggestions have been made on how my study may be improved to yield even better results.
Keywords: National Student Financial Aid Scheme (South Africa); Rhodes University -- Students -- Finance; Education, Higher -- South Africa; Education, Higher -- Finance -- South Africa; Student aid -- South Africa; Welfare state -- South Africa; Student financial aid administration -- South Africa; Student financial aid administration -- South Africa -- Case studies